Impact of air connectivity on tourism, FDI and trade: insight from the Western Cape - Nonyati, Sibusiso (Graduate School of Business (GSB), 2021)
This study investigated the impact of air connectivity on macroeconomic factors, specifically tourism, FDI and trade in the Western Cape, based on quarterly data from 2010 to 2018. The Autoregressive Distributed Lag (ARDL) bounds approach for cointegration was used to assess whether long-run relationships existed between air connectivity and tourism, FDI and trade. The ARDL bounds test found a cointegrated relationship between air connectivity and tourism, FDI and trade respectively. Air connectivity was found to have a positive and significant long-run relationship with tourism This also supports the literature findings that air connectivity improves countries' accessibility and increases tourist arrivals from various markets. This confirms that air connectivity leads to an increase in the number of international tourists visiting the Western Cape, which contributes significantly to the tourism industry and the Western Cape economy. In addition, air connectivity was observed to have a positive but statistically insignificant long-run relationship with FDI and trade respectively. Therefore, this study concludes that air connectivity plays a key role in the economy, specifically regarding tourism through the facilitation of more tourists into the Western Cape. Furthermore, although the study showed positive and insignificant relationships between air connectivity and FDI and trade respectively, air connectivity is related to FDI and trade and these relationships require further investigation. Therefore, it is recommended that policymakers and decisionmakers on the African continent need to have initiatives that support the improvement of air connectivity, especially given that Africa has only a 2.2% market share of global air passengers and less than 10% of the continent's population uses air transport. Other African countries and regions should use a similar approach to what the Western Cape has done to improve the air connectivity between Cape Town and the rest of the world. In addition, investment in airports and airport-related infrastructure is critical and necessary, as poor airport infrastructure has been cited to be one of the obstacles in improving air connectivity in the continent. Furthermore, the development of an air connectivity index for the continent is required. This index will have to take into account the availability of data and the African context. Where data does not exist, a robust plan for the collection of data will also have to be developed. Lastly, the regulation of the aviation market needs urgent attention, starting with an Open Skies policy. The deregulation of air access could play a significant role in improving the African Continent's air connectivity.